PERCEIVED BARRIERS TO ACCESSING AND ACHIEVING ADHERENCE IN ANTIRETROVIRAL THERAPY AMONG HIV PATIENTS AT A RURAL MISSION HOSPITAL IN ZIMBABWE - Marian Chindedza; Fadzai Mutseyekwa; Auxillia Chideme-Munodawafa (European Scientific Journal, ESJ, 2013)
﻿﻿Introduction: Globally, efforts are in place to enhance accessibility to antiretroviral therapy (ART) for people living with HIV. However , many eligible HIV patients in low and middle income countries fail to access ART and when they do, issues of poor adherence emerge as a major drawback to achieving disease control. Background: Bonda is a mission hospital in Manicaland province in Zimbabwe. Reports from the ART clinic revealed that a significant proportion of patients were not adhering to follow-up dates for resupply or getting entirely lost to follow up. Study Purpose: The study aimed to capture the views of patients receiving ART from this rural setting regarding some of the institutional, socioeconomic, religious and cultural factors which may serve as barriers to accessibility and adherence to medication. Study methods: A descriptive cross-sectional study in which qualitative in-depth interviews were carried out to elicit these perceived barriers in a convenience sample of 28 HIV patients accessing services at the centre and a purposive sample of 3 nurses employed in the OI/ART clinic. Findings: Distance and economic constraints particularly related to transport costs were documented to be the major challenges to access and adhering to ART schedules and regimes. Institutional issues such as long waiting times and inadequate levels of staffing were reported but were not perceived by respondents as contributing much to adherence to ART resupply schedules. Also social issues such as religion, culture and stigma were reported to contribute to a marginal extent as barriers to ART access and adherence.